Fertilitas Semen Beku dalam Tris Kuning Telur dan Skim yang Diberi Omega-3 pada Sapi Simmental dengan Ransum Berimbuhan Seng dan Selenium Minimal - Kurnia, Asep; Soeparna, Soeparna; Arifiantini, Raden Iis; Hidayat, Rahmat (Jurnal Veteriner; Vol 19 No 2 (2018)DO - 10.19087/jveteriner.2018.19.2.251, 2018)
This study aims to examine the quality of frozen semen in Tris egg yolk (TEY) extender and skimmed milk extender with or witout omega-3. A total of 18 Simmental bulls belong to Lembang Artificial Insemination Centre were divided into three groups. Each was fed with standard feed (R1), standard feeds supplemented with minimal Se and Zn (R2) and standard feed supplemented with maximal of Se and Zn concentration. Semen were collected using an artificial vagina and were evaluated macro- and microscopically. The semen then were divided into four tubes and each diluted with Skimmed, SkimmedOmega 3, TEY or TEY-O. The semen was then packed into a 0.25 ml straw and equilibrated at 5 oC for 4 hours, then frozen above liquid nitrogen vapor, and stored in liquid nitrogen container (-196 oC). The qualities of frozen semen were evaluated on the motility, individual score, viability and integrity of the plasma membrane of sperms. Sperm motility of bulls fed with standard feed (R1) in TEY extender and R3 in TEY and TEY-Omega-3 extender were higher (p <0.05) compared to the other combinations. No difference was found on the individual score. The viability of sperms in bulls fed with standard feed in SkimmedOmega-3 extender was higher than the other treatments and the highest sperm plasma membrane integrity was demonstrated by sperm in bull feeding with R2 in TEY extender.